Faktor-Faktor yang Mempengaruhi Kejadian Low Back Pain pada Petani Padi di Desa Sei Beras Sekata Kabupaten Deli Serdang - Tarianna Ginting; Lamhot R. Sidabutar; Fetriani Kristian Hura; Hartono Hartono (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aimed to analyze factors associated with LBP among rice farmers in Sei Beras Sekata Village, Sunggal District, Deli Serdang Regency. This study employed an analytic observational design with a cross-sectional approach. A total of 60 respondents were selected using the Slovin formula from a population of 150 farmers. Data were collected through structured questionnaires and direct observation, while pain intensity was measured using the Numerical Rating Scale (NRS). Data were analyzed using univariate and bivariate analyses with the Chi-square test at a significance level of 0.05. The findings showed that LBP was more common among farmers with older age and longer working experience. Age, years of service, and working duration were associated with LBP incidence, while gender, smoking habits, working posture duration, and workload showed no significant association. This study concludes that age, years of service, and working duration contribute to the occurrence of LBP among rice farmers. The limitations of this study include the cross-sectional design, which cannot determine causal relationships, and the relatively limited sample size. Future studies are recommended to use longitudinal designs with larger sample sizes and include more detailed ergonomic assessments. Ergonomic interventions through occupational health education are needed to reduce the risk of musculoskeletal disorders among farmers.